Human security application: the study of media safety in humanitarian missions / Siti Nurbaini Khairi and Noor Nirwandy Mat Noordin - Khairi, Siti Nurbaini; Mat Noordin, Noor Nirwandy (CMIWS and UiTM Press, 2014)
For media personnel, being assigned for humanitarian missions in conflict zone is considered as a one in a lifetime opportunity. However, there were no training and safety courses provided to media people to equip themselves if any casualties happened. The purpose of this study is to find out the steps of preparation to be taken by media organisations and media personnel before sending their people to conflict zones. This includes safety courses, basic medical training and other courses that deem necessary. The objectives of this research are to identify whether any courses or training were taken or given by media personnel before entering conflict zone while covering news for humanitarian missions, to find out whether media personnel understand about the risks in conflict zones and to identify characteristics of selecting media personnel in humanitarian missions.